Oxygen and reactive oxygen species in articular cartilage: modulators of ionic homeostasis. - Gibson, J; Milner, P; White, R; Fairfax, T; Wilkins, R (2008)
Articular cartilage is an avascular tissue dependent on diffusion mainly from synovial fluid to service its metabolic requirements. Levels of oxygen (O(2)) in the tissue are low, with estimates of between 1 and 6%. Metabolism is largely, if not entirely, glycolytic, with little capacity for oxidative phosphorylation. Notwithstanding, the tissue requires O(2) and consumes it, albeit at low rates. Changes in O(2) tension also have profound effects on chondrocytes affecting phenotype, gene expression, and morphology, as well as response to, and production of, cytokines. Although chondrocytes can survive prolonged anoxia, low O(2) levels have significant metabolic effects, inhibiting glycolysis (the negative Pasteur effect), and also notably matrix production. Why this tissue should respond so markedly to reduction in O(2) tension remains a paradox. Ion homeostasis in articular chondrocytes is also markedly affected by the extracellular matrix in which the cells reside. Recent work has shown that ion homeostasis also responds to changes in O(2) tension, in such a way as to produce significant effects on cell function. For this purpose, O(2) probably acts via alteration in levels of reactive oxygen species. We discuss the possibility that O(2) consumption by this tissue is required to maintain levels of ROS, which are then used physiologically as an intracellular signalling device. This postulate may go some way towards explaining why the tissue is dependent on O(2) and why its removal has such marked effects. Understanding the role of oxygen has implications for disease states in which O(2) or ROS levels may be perturbed.